Management and clinical challenges of lupus nephritis presenting with hypotension: a case report - Geetha, Karra; Sasanka, G.; Banu, Meraj Unnisa; Reddy, Pridvineel; Rao, T. Rama (International Journal Of Community Medicine And Public Health, 2025)
Lupus nephritis (LN), a grave sequel of systemic lupus erythematosus (SLE), precipitates substantial renal impairment and engenders noteworthy clinical morbidity. This case report delineates the presentation of a 39-year-old female with antecedent diagnoses of SLE and rheumatoid arthritis, who presented with severe dyspnea (Grade 4), retrosternal chest pain radiating posteriorly, and oliguria. Physical examination unveiled profound hypotension, while initial diagnostic evaluations were congruent with acute kidney injury indicative of LN. Despite robust fluid resuscitation, the patient hypotension persisted, necessitating intricate clinical deliberations. This case encapsulates the multifaceted challenges inherent in the management of lupus nephritis, particularly when complicated by refractory hypotension and multi-organ involvement. It accentuates the imperativeness of prompt diagnostic acuity and an integrative therapeutic paradigm. Additionally, it elucidates the rationale underpinning pivotal clinical decisions while addressing the nuances of such a formidable clinical scenario.